Hrvatske povijesne i etiološke predaje o ilirskoj kraljici Teuti - Dragić, Marko, filolog (Array, 2018)
King Agron, the unifier of the Illyrian lands, died in the year 231 B.C. and was inherited by his wife Teuta. Through time people have woven tales about queen Teuta that are told even nowadays. Teuta is said to be the most beautiful queen and daughter of a medicine woman from Narona. According to tales, Teuta resided on Šolta, in Dol on Hvar, on Svetac near Vis (once called the island of St. Andrew), in Jezero near Jajce, Borak near Široki Brijeg and in Risan in the Bay of Kotor. She soon came in conflict with the Romans and was defeated. Illyrian military commander Demetrius of Pharos disobeyed Teuta and sided with the Romans. According to the tales from Vis, Teuta, not being able to stand watching the Romans pillage her kingdom, ended her life on Svetac by jumping out of her fort. In the Bay of Kotor and other parts of Montenegro it is told that Teuta jumped from a cliff above Risan. The paper cites and interprets about forty historical and etiological tales which were recorded from 2001 to 2017. The tales were originally recorded in Croatia, Bosnia and Herzegovina and Montenegro.